Tamarind seed polysaccharide (TSP) uses in ophthalmic drug delivery - Matheus Augusto de Castro; Wallace Mateus Prata; Armando Silva Cunha (São Paulo State University (UNESP), 2021)
At present, ophthalmic drug delivery remains a major challenge, given the eye's prot ective structure and susceptibility to irritation, resulting in poor patient adherence. In order to overcome these constraints, new formulations are continually being developed. The inclusion of Galactoxyloglucan (Tamarind seed polysaccharide (TSP) in such formulations, a natural substance extracted from the seeds of Tamarindus indica, has shown great potential due to its physico - chemical properties, high biocompatibility and safety profile. Such properties, have led to its use in formulations for the treatment of dry eye disease, glaucoma, and bacterial keratitis, as well as in dilating eye drops used in eye examinations. In this article, we highlight the most recent TSP - based ophthalmologic formulations, which indicate that this polymer is a strong candidate to reduce adverse effects, improve patient tolerability and drug bioavailability.